Generalized Hadamard well-posedness for infinite vector optimization problems. (3rd October 2017) - Peng, Z. Y.; Long, X. J.; Wang, X. F.; Zhao, Y. B.
Abstract: In this paper, we study the generalized Hadamard well-posedness of infinite vector optimization problems (IVOP). Without the assumption of continuity with respect to the first variable, the upper semicontinuity and closedness of constraint set mappings are established. Under weaker assumptions, sufficient conditions of generalized Hadamard well-posedness for IVOP are obtained under perturbations of both the objective function and the constraint set. We apply our results to the semi-infinite vector optimization problem and the semi-infinite multi-objective optimization problem.